Evaluating the ecological impacts of salvage logging: can natural and anthropogenic disturbances promote coexistence?. Issue 6 (1st June 2016) - Royo, Alejandro A.; Peterson, Chris J.; Stanovick, John S.; Carson, Walter P.
Abstract: Salvage logging following windthrow is common throughout forests worldwide even though the practice is often considered inimical to forest recovery. Because salvaging removes trees, crushes seedlings, and compacts soils, many warn this practice may delay succession, suppress diversity, and alter composition. Here, over 8 yr following windthrow, we experimentally evaluate how salvaging affects tree succession across 11 gaps in Eastern deciduous forests of Pennsylvania, wherein each gap was divided into salvaged and control (unsalvaged) halves. Our gaps vary in size and windthrow severity, and we explicitly account for this variation as well as variation in soil disturbance (i.e., scarification) resulting from salvaging so that our results would be generalizable. Salvage logging had modest and ephemeral impacts on tree succession. Seedling richness and density declined similarly over time in both salvaged and unsalvaged areas as individuals grew into saplings. The primary impact of salvaging on succession occurred where salvaging scarified soils. Here, salvaging caused 41 to 82% declines in sapling abundance, richness, and diversity, but these differences largely disappeared within 5 yr. Additionally, we documented interactions between windthrow severity and scarification. Specifically, low‐severity windthrow and scarification combined reinforced dominance by shade‐tolerant and browse‐tolerant species ( Acer pensylvanicum, Fagus grandifolia ). In contrast, high windthrow severity and scarification together reduced the density of a fast‐growing pioneer tree ( Prunus pensylvanica ) and non‐tree vegetation cover by 75% and 26%, respectively. This reduction enhanced the recruitment of two mid‐successional tree species, Acer rubrum and Prunus serotina, by 2 and 3‐fold, respectively. Thus, our findings demonstrate that salvaging creates novel microsites and mitigates competing vegetation, thereby enhancing establishment of important hardwoods and promoting tree species coexistence. Our results, coupled with an assessment of 27 published post‐windthrow salvage studies, suggest short‐term studies may overestimate the impact of salvaging on regeneration. We conclude that the ecological costs and benefits of salvaging depend upon the variation in canopy and soil disturbance severity as well as the timescale at which effects are evaluated. Thus, our findings are inconsistent with the view that salvaging inexorably undermines plant diversity; rather we suggest salvaging can promote tree species coexistence within various contexts.